Synthesis and electrochemical properties of environmental free l-glutathione grafted graphene oxide/ZnO nanocomposite for highly selective piroxicam sensing - N. Dhanalakshmi; T. Priya; S. Thennarasu; S. Sivanesan; N. Thinakaran (Elsevier, 2021)
A simple and reliable strategy was proposed to engineer the glutathione grafted graphene oxide/ZnO nanocomposite (glutathione-GO/ZnO) as electrode material for the high-performance piroxicam sensor. The prepared glutathione-GO/ZnO nanocomposite was well characterized by X-ray diffraction (XRD), Fourier transform infrared spectrum (FTIR), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and differential pulse voltammetry (DPV). The novel nanocomposite modified electrode showed the highest electrocatalytic activity towards piroxicam (oxidation potential is 0.52 V). Under controlled experimental parameters, the proposed sensor exhibited good linear responses to piroxicam concentrations ranging from 0.1 to 500 μM. The detection limit and sensitivity were calculated as 1.8 nM and 0.2 μA/μM·cm2, respectively. Moreover, it offered excellent selectivity, reproducibility, and long-term stability and can effectively ignore the interfering candidates commonly existing in the pharmaceutical tablets and human fluids even at a higher concentration. Finally, the reported sensor was successfully employed to the direct determination of piroxicam in practical samples.